2021
DOI: 10.1590/fst.05020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti anemic prospective of natural iron sources in lactating women- an ignored important segment of Pakistani population

Abstract: Almost entire segment of expecting and breastfeeding mothers in Pakistan are severely affected by iron deficiency anemia (IDA) with predictable prevalence of 50% and as severe public health problem in lactating mothers, has worldwide pervasiveness. Commonly used synthetic iron sources provoke complications. Thus, food sources are preferred due to high bioavailability and sustainability. The present study was done on various natural and synthetic iron sources evaluated for proximate composition, mineral matter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Several studies have revealed that anaemia prevalence is not uniform among lactating and non-lactating mothers. 21 22 Lactating mothers are considered a more vulnerable group than non-lactating mothers as they are physiologically and nutritionally at a higher risk of iron deficiency and could acquire anaemia during their pregnancy. 23 24 Besides, lactating mothers require highly nutritious food to produce an adequate quantity of milk in addition to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that anaemia prevalence is not uniform among lactating and non-lactating mothers. 21 22 Lactating mothers are considered a more vulnerable group than non-lactating mothers as they are physiologically and nutritionally at a higher risk of iron deficiency and could acquire anaemia during their pregnancy. 23 24 Besides, lactating mothers require highly nutritious food to produce an adequate quantity of milk in addition to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Los principales determinantes de la anemia en el país son, prematuridad, bajo peso al nacer, disminución de la lactancia materna, poca adherencia al tratamiento, ingesta de alimentos bajo en hierro, alta prevalencia de infecciones tanto diarreicas como respiratorias, inadecuada higiene, y falta de saneamiento de agua y desconocimiento en los actores. (MIDIS, 2018) Por otro lado, Abdullah, et al (2020), Sostuvieron que: La anemia es una condición en la cual el nivel de hemoglobina en sangre es reducido de la concentración normal (Hb <11 g / dL en lactancia mujeres) y dificulta el suministro de oxígeno a la sangre que angustia grave la salud de la madre y el niño, desarrollo del recién nacido, competencia laboral, astucia y poder adquisitivo del empleo. (p. 1) Además, el Colegio Médico del Perú en (adelante CMP, 2018), refiere que la reducción de la anemia significa volver al estado normal los niveles de hemoglobina.…”
Section: )unclassified
“…Hence, the purpose of this conceptual study was to explore the occurrence of individual evolution. Through observing the prevalence of myopia in a selected family, we proposed a conjecture that there are changes in the traits and individuals' genetic predisposition to myopia, and such defectiveness can be passed to the next generation through a genetic pathway (Felberbaum & Küpker, 2015;Abdullah et al, 2020;Altuntas & Korukluoglu, 2019;Kanak & Yilmaz, 2020). In addition, we hypothesized the feedback pathway of individual evolution and its underlying genetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%